Effets Des Technologies Membranaires Sur Les Caracteristiques Physicochimiques Des Extraits De Fruits De La Passion (Passiflora Edulis) - Casimir Anauma Koko; Benjamin Kan Kouamé; Massé Diomandé; Christiane Eunice Adjoua Boko; Félix Adjé; Emmanuel Nogbou Assidjo; Georges N’guessan Amani (European Scientific Journal, ESJ, 2018)
The passion fruit or grenadilla is usually consumed in the form of juice and its pleasant intensive aroma and flavor make it an attractive element for the food industry. The objective of the present work is to determine the effects of membrane technologies such as tangential microfiltration and reverse osmosis on the physicochemical characteristics of passion fruit extracts. The characteristics of the various extracts were determined according to conventional methods. In addition, statistical methods were applied to the data collected in order to determine the effects of membrane technologies. The results showed a yield of 89.33% for the extraction of the microfiltered juice and a volume reduction factor of 16.75 for the concentrate. In addition, the microfiltration-concentration process significantly (p <0.05) influenced the physicochemical parameters of the extracts produced. Thus, tangential microfiltration made it possible to clarify the crude extract by changing from a turbidity of 89.23 ± 1.71 to 0.72 ± 0.02 NTU. It has also resulted in a significant decrease in pH and flavonoids contents. Principal component analysis confirmed the existence of differences between the extracts produced despite the various correlations between their characteristics. It revealed that the JB and CMFT extracts are characterized by their high pH and low density. On the other hand, the COI extract is characterized by its brix degree, viscosity, conductivity and high vitamin C content. In addition, reverse osmosis has the advantage of concentrating the compounds of interest of clarified juice with a concentration factor ranging from 2.15 to 9.39.